The Context Meaning of Deixis in Maher Zain Selected Songs - Khasanah, Yatul; Rahmat, Hery (EDUKASI, 2024)
The deixis and its contextual meaning in the Maher Zains song are discussed in this study. Content analysis was the form of research used in the descriptive qualitative approach of research methodology. This research uses a practical methodology, based on the conceptualization of deixis by Alan Cruse, which includes person, spatial, temporal, social, and discourse deixis. The purpose of the study is to evaluate the various deixis types and its reference meanings through analysis and interpretation of Maher Zain's "Forgive Me" album lyrics. The results show that Maher Zain's "Forgive Me" album does, in fact, use a variety of deixis in its lyrics, including person, spatial, temporal, social, and discourse deixis. First and second pronouns are included in the personal deixis, which represents the characters and roles in the song lyrics. Whereas temporal deixis denotes the relative time of speech events, and spatial deixis specifies the location of events. Most of the album's tracks use social deixis, which represents social standing and a person's proximity to their mother, God, and the social surroundings. Finally, there are instances of discourse deixis in one song, including the phrases "And, But, So." It describes the connection between a speech and the speech that came before it.